A new nitrobenzoxadiazole-based GSTP1-1 inhibitor with a previously unheard of mechanism of action and high stability - Chiara Fulci; Dante Rotili; Anastasia De Luca; Lorenzo Stella; Blasco Morozzo della Rocca; Mariantonietta Forgione; Veronica Di Paolo; Antonello Mai; Mattia Falconi; Luigi Quintieri; Anna M. Caccuri (Taylor & Francis Group, 2017)
Context: The nitrobezoxadiazole derivative NBDHEX is a potent inhibitor of glutathione transferase P1-1 (GSTP1-1) endowed with outstanding anticancer activity in different tumor models. Objective: To characterize by in vitro biochemical and in silico studies the NBDHEX analogues named MC2752 and MC2753. Materials and methods: Synthesis of MC2752 and MC2753, biochemical assays and in silico docking and normal-mode analyses. Results: The presence of a hydrophobic moiety in the side chain of MC2753 confers unique features to this molecule. Unlike its parent drug NBDHEX, MC2753 does not require GSH to trigger the dissociation of the complex between GSTP1-1 and TRAF2, and displays high stability towards the nucleophilic attack of the tripeptide under physiological conditions. Discussion and conclusion: MC2753 may represent a lead compound for the development of novel GSTP1-1 inhibitors not affected in their anticancer action by fluctuations of cellular GSH levels, and characterized by an increased half-life in vivo.